2007
DOI: 10.1049/iet-map:20050289
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a bi-periodic magnetoinductive waveguide: comparison with theory

Abstract: Magnetoinductive waves propagating along a line consisting of two kinds of metamaterial elements are studied. Both elements are made up by the same metallic loop but are loaded by different capacitors resulting in different resonant frequencies. The dispersion characteristics are derived from phase and amplitude measurements for the cases when the line consists of (i) identical elements and (ii) of alternating elements. Both planar (elements in the same plane as the axis of the line) and axial (elements perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Occasionally, especially when the elements are very close, this coupling effect is not negligible and will have a substantial effect on the properties of the metamaterials. Recent studies have shown that the resonance coupling effect between split-ring resonators (SRR) can introduce magnetoinductive waves [10][11][12][13][14][15][16] In our previous theory work [27], another kind of coupling mechanism between resonance elements, …”
mentioning
confidence: 99%
“…Occasionally, especially when the elements are very close, this coupling effect is not negligible and will have a substantial effect on the properties of the metamaterials. Recent studies have shown that the resonance coupling effect between split-ring resonators (SRR) can introduce magnetoinductive waves [10][11][12][13][14][15][16] In our previous theory work [27], another kind of coupling mechanism between resonance elements, …”
mentioning
confidence: 99%
“…The propagation in linear arrays of SRRs in axial (i.e., wavevector is in the same direction of the magnetic dipole moment describing the SRR) or transverse (i.e., wavevector is in the transverse direction of the magnetic dipole moment describing the SRR) configuration has been studied experimentally in [2], and similar works (including theory) have been shown in [3][4][5]. The dispersion properties of a biperiodic linear array of SRRs (contiguous loops are loaded with different capacitances) have been shown experimentally in [6] to support MI waves in two distinct frequency bands. The same phenomenon has been studied thoroughly in linear arrays in [7] by having also a unit cell with two SRRs whose relative distance is smaller than the period.…”
Section: Introductionmentioning
confidence: 91%
“…Tailoring dispersion equations of biatomic metamaterials was demonstrated experimentally in Refs. [112,113].…”
Section: Dispersion Equations Of Slow Magnetoinductive Wavesmentioning
confidence: 99%